Fabrication and characterization of few-mode fiber bragg gratings for mode conversion and sensing applications / Muhammad Mahmood Ali - Muhammad , Mahmood Ali (2016)

(untitled)
Few-mode fibers (FMFs ) have unveiled a new horizon to find various applications in new photonic devices. Currently, they have gained a great interest in optical communication and sensing technologies, particularly in the field of space division multiplexing technology to increase the transmission bandwidth and to overcome the capacity limitations of standard SMF-28 fiber. FMF offer several distinct features from single mode fibers and multimode fibers, in terms of medium core size which is capable of accommodating several transverse modes (2-6 modes) and supporting multiple transmission channels through mode-division multiplexing (MDM). The inscription of grating structure in FMF produces intriguing grating device that offers more than one Bragg wavelength where each wavelength can be associated to one or two transverse modes in the fiber. Therefore, it is essential to investigate and precisely characterize the several properties of these modes such as coupling between modes and their sensitivities to the ambient environment, with their applications. In this thesis, the fabrication of Bragg gratings (FM-FBGs) on two-mode (2MF) and four-mode (4MF) step index fibers will be discussed. It is mentioned that the environmental effects such as pre-stress conditions during fabrication, can alter the grating period which may be slightly deviate from the period of phase mask. Therefore a non-destructive approach based on Optical Imaging Technique (OIT) is proposed for measuring the period of an FBG. OIT has been used for the accurate measurement of grating period of FBGs inscribed in single mode fiber and in few-mode fibers before experimental characterization. Thereafter the FM-FBGs are analysed experimentally through selective mode excitation using binary phase plates. The reflected mode intensity profiles at each resonant Bragg wavelength under different mode excitation conditions are analysed to confirm the involved resonant iv spatial modes. The mode coupling, such as self-mode and cross-mode coupling, occurring inside the fabricated FM-FBGs, is investigated. The measured transmission and reflection spectra are compared with the simulation results. Cross-mode coupled wavelengths offer the feature of conversion between the two associated modes and the conversion efficiency can be associated with the grating strength. Thereafter, the modal sensitivities of FM-FBGs to temperature and refractive index change have been investigated. Chemical etching technique is performed to remove the cladding of FM-FBG and to enhance the sensitivity of to the ambient refractive index change.